The effects of dietary kefir and low molecular weight sodium alginate on serum immune parameters, resistance against Streptococcus agalactiae and growth performance in Nile tilapia (Oreochromis niloticus) - Van Doan H. (2017)
© 2017 Elsevier Ltd The present study evaluates the effects of dietary kefir and low molecular weight sodium alginate (LWMSA) (singular or combined) on non-specific immune response, disease resistance and growth performance of Nile tilapia (Oreochromis niloticus). Fish with average weight of 18.60 ± 0.04 g were supplied and randomly stocked in sixteen glass tanks (150 L) at density of 20 fish per tank. Fish were fed experimental diets as follows: 0 g kg −1 LMWSA (Control, Diet 1), 10 g kg −1 LMWSA (Diet 2), 40 g kg −1 kefir (Diet 3), and 10 g kg −1 LMWSA + 40 g kg −1 kefir (Diet 4) for 50 days. At the end of the feeding trial, serum lysozyme (SL), phagocytosis (PI), respiratory burst (RB), and alternative complement (ACH50) activities as well as growth performance were measured. Singular and combined administration of kefir and low molecular weight sodium alginate (LMWSA) significantly increased serum SL, PI, RB, and ACH50 activities compared control group (P  <  0.05); the highest innate immune responses were observed in fish fed combinational diet (kefir + LMWSA) (P  <  0.05). The results of experimental challenge revealed significantly higher resistance against Streptococcus agalactiae in fish fed supplemented diets and the highest post challenge survival rate was observed in synbiotic diet (P  <  0.05). Similar results obtained in case of growth parameters. Feeding on supplemented diet significantly improved SGR and FCR and the highest growth parameters was observed in fish fed synbiotic diet (P  <  0.05). These finding revealed that combined administration of dietary kefir and LMWSA can be considered for improving immune response, disease resistance and growth performance of Nile tilapia.